La Justicia como un valor Fundamental en la Constitución de la República Bolivariana de Venezuela - The Justice as a Fundamental Righ in the of the Republic of Venezuela - Olivares García, Suying (Frónesis, 2019)
ResumenLa presente investigación analiza la justicia como un valor fundamental bajo la concepción de un Estado Social de Derecho y de Justicia, previsto en el Texto Constitucional de 1999. Sin embargo, el Texto Constitucional vigente, no consagra una definición de lo que debe entenderse por Estado Social de Derecho y de Justicia; en este sentido, emprenderemos el estudio de algunas sentencias que el Tribunal Supremo de Justicia ha dictado sobre la materia a los efectos de aproximarnos a sus conceptualizaciones.Abstract This research analyzes justice as a fundamental value under the conception of a Social State of Law and Justice, provided for in the 1999 Constitutional Text. The current Constitutional Text does not establish a definition of what should be understood by the Social State of Law And Justice; In this sense, we will undertake the study of some judgments that the Supreme Court of Justice has dictated on the matter in order to approach its conceptualizations.